LEVEL OF SATISFACTION OF PATIENTS OF BPJS HEALTH ON QUALITY OF SERVICE IN PUSKESMAS BAILANG, MANADO CITY - Trisna Awalinda; Julianus Ake; M Consolatrix da Silva (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2019)
Background: patient satisfaction is one indicator of the success of health services and an important aspect that must be achieved by all health services institutions. Quality services are a form of patient acknowledgment of services received. Some studies employ satisfaction levels to determine a patient’s satisfaction. Aim: This study aims to examine the relationship between the quality of service and the level of patient satisfaction of health care participants in outpatients at the Bailang Public Health Center. Method: This study uses a cross-sectional design. Using a purposive sampling technique, as many as 37 respondents agreed to use. Service quality data is collected using a questionnaire sheet. Data were analyzed using the Fisher Exact Test statistical test, with a significance level of 95% (p <0.005). Results: the analysis showed a significant relationship (p = 0.014) between service quality and patient satisfaction. This research shows that service quality greatly increases patient satisfaction. Improvement of the quality of services provided will increase patient satisfaction. The findings in this study are expected to be a reference to improve the quality of BPJS services in the general public and specifically at the Bailang Puskesmas.